PENGARUH PERSEPSI NILAI KONSUMEN TERHADAP MINAT BELI PRODUK PRIVATE LABEL LOTTE MART DI KOTA PEKANBARU - Vivin Mayang Sari; Eliza '; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study was 1) to determine the Effect of Costumer Perceived Value Against Intention To Buy Private Label Lotte Mart in the city of Pekanbaru and 2) identify dominant variables affecting intention to buy. After doing a literature review and hypothesis formulation, the primary datais obtained by spreading questionaries to 50 respondents who met the criteria,which are obtained using purposive sampling technique. Then the data is analyzed both quantitatively and qualitatively. Qualitative analysis is the interpretation of the data obtained in the field and analysis of open answers given by the respondents, whereas the quantitative analysis include: validity test, reliability test, the classic assumption test, multiple linear regression analysis, F-test, t-test, and analysis coefficient of determination. The result of this study shows that brand loyalty (X2), perceived price (X3), and perceived quality (X4) proved significantly affect intention to buy (Y). Perceived quality affect the consumer intention to buy higher than the effect of perceived price and brand loyalty with a regression coefficient of 0.551 significant at the 0.013 level. Keywords: Costumer Perceived Value, Private Label, and Intention To Buy